URBAN TRANSFORMATION ON THE WATERFRONTS OF VALENCIA AND BILBAO - Gironés, Pau Caparrós (PEOPLE: International Journal of Social Sciences, 2019)
This article analyzes cases of urban transformation carried out in the waterfront areas of Valencia and Bilbao, in Spain. Through the implementation of urban regeneration and transformation strategies, these two cities have transformed most of their waterfront areas during the last decade of the 20th century and the first decade of the 21st century. Old industrial sites have been transformed into residential and service spaces, following the lead of other European cities like Liverpool and Hamburg, which also had former port sites. Comparing both of these initiatives of waterfront transformation reveals two very different processes. Two dimensions has been compared: the governance of the intervention plans drawn up and the social dimension of the interventions. The article set out the following questions. What are the perspectives of the urban planning professionals that participated in the transformation of the coasts of Valencia and Bilbao? And, what is the fulfillment of the project objectives and the changes produced in the urban environment of the two areas?